(untitled) (Perspectivas em Psicologia, 2025)
This article endeavors to present a phenomenological portrayal of the concept of mental health, employing the philosophical insights of Maurice Merleau-Ponty and Martin Heidegger as guiding principles. The embodied nature of existence, intersubjectivity, and the existential-phenomenological proposition of being-in-the-world and being-towards-the-world, as conceptualized by Maurice Merleau-Ponty, will be juxtaposed with the contemporary psychopathological phenomenological notions put forth by Thomas Fuchs and Giovanni Stanghellini. Moreover, the argumentative discourse will be fortified in the subsequent section of the article, drawing analogies between the preceding analysis and the motivating factors outlined in the works of Martin Heidegger. This exploration will specifically delve into Heidegger’s existential analysis of Dasein, emphasizing the postulate of being-in-the-world as an encompassing environmental existence that includes society. In this context, the societal conventions and norms will be examined as causal factors, giving rise to what Heidegger would characterize as inauthenticity.